2023
DOI: 10.1186/s12872-023-03452-z
|View full text |Cite
|
Sign up to set email alerts
|

Association between weight-adjusted-waist index and risk of cardiovascular diseases in United States adults: a cross-sectional study

Haiyang Fang,
Feng Xie,
Kai Li
et al.

Abstract: Background As a new obesity-related index, the weight-adjusted-waist index (WWI) appears to be a good predictor of cardiovascular disease (CVD) in East Asian populations. This study aimed to validate the association between WWI and CVD in United States (US) adults and also evaluate its relationships with the prevalence of specific CVDs. Methods The data were obtained from the 2009–2016 National Health and Nutrition Examination Survey. WWI was calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…In addition to being associated with T2DM, WWI is significantly associated with a variety of cardiovascular diseases and poor prognosis. A prospective cohort study from China included 10,338 nonhypertensive subjects with a mean follow-up of 6 years and found that high WWI was significantly linked to an increased risk of hypertension (24).In a cross-sectional study that included 21,040 subjects, Fang H et al found that high levels of WWI were significantly associated with an elevated risk of development of CVD, especially prominent in those under 50 years of age, suggesting that WWI may be an interventional indicator for reducing the risk of cardiovascular disease in the general adult population (25). In a prospective cohort study (n=26822) with a mean follow-up of 69 months, elevated levels of WWI were found to be independently correlated with an increased risk of cardiovascular mortality and all-cause mortality (26).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to being associated with T2DM, WWI is significantly associated with a variety of cardiovascular diseases and poor prognosis. A prospective cohort study from China included 10,338 nonhypertensive subjects with a mean follow-up of 6 years and found that high WWI was significantly linked to an increased risk of hypertension (24).In a cross-sectional study that included 21,040 subjects, Fang H et al found that high levels of WWI were significantly associated with an elevated risk of development of CVD, especially prominent in those under 50 years of age, suggesting that WWI may be an interventional indicator for reducing the risk of cardiovascular disease in the general adult population (25). In a prospective cohort study (n=26822) with a mean follow-up of 69 months, elevated levels of WWI were found to be independently correlated with an increased risk of cardiovascular mortality and all-cause mortality (26).…”
Section: Discussionmentioning
confidence: 99%
“…This research observed a possible link between WWI and a higher risk of moderate/severe periodontitis, with variations in different age groups. The increase in WWI may reflect the dysfunction of adipose tissue, leading to the synthesis and secretion of various pro-inflammatory cytokines [ 27 ]. Obesity may contribute to periodontitis through different pathological mechanisms, including changes in adipokine release levels, induction of inflammatory reactions, immune dysregulation, and dysbiosis of oral microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…This allows for a more precise and comprehensive assessment of central obesity, thereby providing a clearer depiction of the relationship between obesity and cognitive function. Recent studies have demonstrated effectiveness of WWI in differentiating muscle mass from fat mass, leading to its broader application in various medical domains including metabolic diseases, kidney diseases, and cardiovascular diseases, among others ( 31 33 ). Furthermore, WWI has shown a greater correlation and predictive power in some diseases compared to traditional obesity indices ( 34 , 35 ).…”
Section: Discussionmentioning
confidence: 99%